The effect of social network marketing on online purchase intention: a model in the health market - Toktam Salari; Omar Yousefi; D. Anand (Shahid Beheshti University of Medical Sciences, 2022)
Background: This study aimed to investigate the role of social network marketing on the intention of online shopping in the health market. Methods: This study was a descriptive survey. The data collection tool was a researcher-made questionnaire and its validity was confirmed by university professors and its reliability was confirmed by Cronbach's alpha test. Students of Islamic Azad University, Kermanshah Branch were statistical population and sample selected with random sampling.  Considering that students are active and knowledgeable groups in the field of social networks, therefore, the effect of social network marketing on brand awareness and perceived security on the willingness to buy online in this group of social was investigated. SPSS software, One-Sample T-Test, and the Friedman test were used to rank the variables. AMOS was used to rate the importance of each component. Results: The men's groups were up 57% of the population, and the age group of 18 to 22 years was the largest. The correlation coefficient of brand awareness, Perceived security component, advertising component, promotion component, Information sharing, and creating friendship groups were 0.76, 0.74, 0.59, 0.55, 0.49, and 0.47, respectively. Data analysis showed that the significance differences of advertising, advertising, creating friendship groups, information sharing, brand awareness, and perceived security were 0.12, 0.16, 0.39, 0.24, 0.25 and 0.17, respectively. A significant difference was between the total observed variables and the latent variable in the proposed model all correlation coefficients have a significant difference. Conclusion: It is necessary to use new digital marketing strategies in health marketing to maximize the efficiency of marketing costs and create a higher rate of return.